1990
DOI: 10.1016/s0735-1097(10)80076-2
|View full text |Cite
|
Sign up to set email alerts
|

Doppler echocardiographic measurement of pulmonary artery pressure from ductal Doppler velocities in the newborn

Abstract: The ductal flow velocities in 37 newborns (group 1: persistent pulmonary hypertension [n = 16], transient tachypnea [n = 3], other [n = 2]; group 2: respiratory distress syndrome [n = 16]) were prospectively evaluated by Doppler ultrasound for the purpose of deriving systolic pulmonary artery pressures. Maximal tricuspid regurgitant Doppler velocity in 21 of these patients was used to validate the pulmonary artery pressures derived from ductal flow velocities. There was a significant linear correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 24 publications
2
48
0
2
Order By: Relevance
“…In Patients with unidirectional ductal shunting the correlation coefficient was r=0.95(p<0.001; SEE=8mmHg). 4 In the same year Sinder (1990) Our results are in concordance with the results of studies done previously.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In Patients with unidirectional ductal shunting the correlation coefficient was r=0.95(p<0.001; SEE=8mmHg). 4 In the same year Sinder (1990) Our results are in concordance with the results of studies done previously.…”
Section: Discussionsupporting
confidence: 91%
“…It was r=0.96 between end diastolic aortic to main pulmonary pressure gradient and minimum Doppler velocity. 5 While performing similar study in 37 newborns, Musewe et al (1990) found a significant linear correlation between catheter measured SPAP and pulmonary artery systolic pressure derived from ductal Doppler velocities. In Patients with unidirectional ductal shunting the correlation coefficient was r=0.95(p<0.001; SEE=8mmHg).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To date, echocardiographic studies have been limited to the differentiation of PPHN from congenital heart disease (13), the assessment of atrial shunting (14), and the development of indirect M-mode indices for early identification of infants with PPHN (15). More recent Doppler methods include the use of acceleration time (16), the mean velocity of pulmonary blood flow (17), ductus venosus blood velocity (18), velocity across the PDA (19,20), and regurgitant jet velocity across the tricuspid valve (16,20,21). Estimation of the systolic PAP from the peak velocity of the TR jet is the most accurate method and is easy to measure (16,21), but it is not always available.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure gradient (PG) driving blood through an orifice can be calculated according to the simplified Bernoulli equation as PG54V 2 (mmHg), where V represents the peak jet velocity, not accounting for orifice geometry and blood viscosity [16,18]. Consequently, the peak jet velocity of pulmonary insufficiency [19] as well as peak flow velocities across a ventricular septal defect [20,21] or patent ductus arteriosus [22] allow for calculations of Ppa. However, tricuspid valve regurgitant jet is the most widely used for this purpose [23].…”
Section: Diagnostic Value Of Echocardiography and Its Role In Screenimentioning
confidence: 99%